2021
DOI: 10.1039/d0na01050b
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in sensing application of metal nanoarchitecture-enhanced fluorescence

Abstract: Fluorescence analytical method, as a real time and in situ analytical approach to target analytes, can offer advantages of high sensitivity/selectivity, great versatility, non-invasive measurement and easy to transmit over...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 165 publications
2
16
0
Order By: Relevance
“…The red shift of the QD nanocrystal photoluminescence is attributed to the interactions between the permanent dipole moment of the QD nanocrystals and the dipole moment induced in the AgNPs. 20 A similar change in the RhB fluorophore emission peak wavelength and line width was found ( Figure S12 ). Relatively low quantum yield (QY) molecules at a concentration of 10 –8 M were also investigated such as crystal violet (CV) ( Figure S13 ), and a significant increase of ∼34-fold in PEF intensity was seen.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The red shift of the QD nanocrystal photoluminescence is attributed to the interactions between the permanent dipole moment of the QD nanocrystals and the dipole moment induced in the AgNPs. 20 A similar change in the RhB fluorophore emission peak wavelength and line width was found ( Figure S12 ). Relatively low quantum yield (QY) molecules at a concentration of 10 –8 M were also investigated such as crystal violet (CV) ( Figure S13 ), and a significant increase of ∼34-fold in PEF intensity was seen.…”
Section: Resultssupporting
confidence: 71%
“…Studies have reported that PEF emission spectra from QD nanocrystals are spectrally red shifted in addition to an enhancement in fluorescence signal strength when they are coupled with localized plasmons. 20 Additionally, it has been reported that the red shift of the QD nanocrystal photoluminescence can be assigned to the exchanges between the transition dipole moments or electronic states of the QD nanocrystals and the dipole moment induced in the AgNPs, 20 while the fluorescence emission fwhm of QD nanocrystal emitters is reduced as a result of the stronger interaction with localized plasmons. 20 This is in agreement with theoretical calculations ( Figure 2 c, as outlined above), which showed that negatively charging the AgNP can create a new plasmon resonance frequency more in resonance with the QD emission frequency, leading to a stronger interaction of the QD nanocrystal emitter with localized plasmons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, by exploiting various metal nanoarchitectures to manipulate fluorescence, both increased fluorescence quantum yield and improved photostability can be realized. [11].…”
Section: Introductionmentioning
confidence: 99%